Spontaneous filtering bleb with subsequent secondary glaucoma June consultation #1. Issue 7 (July 2021) - Berryman, Jefferson; Samuelson, Thomas W.
Abstract : A healthy, 32-year-old myopic woman presented with hypotony due to a spontaneous, perilimbal filtration bleb that later occluded with PAS, resulting in intractably elevated IOP and visual field loss. Abstract : A 32-year-old previously healthy woman was referred for evaluation and management of newly diagnosed hypotony in the right eye. Her ocular history was significant only for moderate myopia and an idiopathic Horner syndrome in the left eye diagnosed at age 13. The patient endorsed a history of fluctuating and decreasing vision in the right eye over the past 6 months. She denied any ocular pain, previous ocular surgery, or recent trauma. The patient was otherwise healthy and denied any previous autoimmune disease or systemic infection. She wore soft, daily disposable contact lenses and reported no abnormalities on previous routine eye examinations. At presentation, the patient's uncorrected distance visual acuity was 20/25 in the right eye and 20/200 in the left. Lensometry revealed a previous refraction of −3.00 + 0.50× 150 in the right eye and −4.00 + 1.75× 174 in the left. Intraocular pressures (IOPs) were 4 mm Hg and 15 mm Hg by applanation, and central corneal thicknesses were 573 μm and 564 μm in the right and left eyes, respectively. Slitlamp examination revealed an area of scleral thinning near the limbus in the right eye from 5 to 7 o'clock with mild overlying chemosis (Figure 1 ). Gonioscopy showed an open angle with mild trabecular meshwork pigmentation in both eyes without any cyclodialysis clefts, peripheral anterior synechiae (PAS), or other abnormalities. Dilated fundus examination was significant for mild optic nerve edema and chorioretinal folds in the right eye. Optical coherence tomography (OCT) of the optic nerve confirmed mild disc edema (Figure 2 ) and OCT of the macula confirmed mild chorioretinal folds. Anterior segment OCT (AS-OCT) and ultrasound biomicroscopy failed to show any other abnormalities. The patient was initially observed without treatment and presented urgently approximately 1 month later with decreased vision and ocular discomfort. Repeat examination revealed an IOP of 31 mm Hg and a focal area of PAS to the previous area of scleral thinning (Figure 3 ). In one respect, the newly elevated IOP was considered transiently therapeutic to help reverse the hyperopic shift, disc edema, and hypotony-related maculopathy. However, the situation quickly became more worrisome when shortly thereafter the IOP elevated to 55 mm Hg at subsequent follow-up, and multiple IOP-lowering medications were initiated. Over numerous additional visits, the patient's IOPs ranged from 30 to 39 mm Hg in the right eye despite rapidly advancing to maximally tolerated medical therapy including acetazolamide. She was noted to have a new relative afferent pupillary defect of the right eye, and Humphrey visual fields showed early arcuate defects (Figure 4 ). What would be your approach to managing this healthy, young, myopic woman who presented with hypotony due to a spontaneous, perilimbal filtration bleb that later occluded with PAS, resulting in intractably elevated IOP and field loss? What is the differential diagnosis? Would you perform a systemic workup for her initial scleral thinning, and if so, what would you check? Would you intervene for her elevated IOP in the right eye? If so, what would be your surgical approach?